DEVELOPMENT OF MICRO SMALL AND MEDIUM ENTERPRISES (MSMEs) BASED ON CREATIVE ECONOMY IN IMPROVING COMMUNITY ECONOMIC INCOMES - Sumarsid Sumarsid; Hartatik Hartatik; Ahmad Mukhlis; Ahdi Topan Sofyan (International Journal of Economy, Education and Entrepreneurship, 2022)
This research aims to explore the development of creative economic development strategies to increase people's income and identify inhibiting factors in developing MSMEs to increase revenue, mainly for tempe owners and traders. The MSME Creative Economy in the Tempe cases can improve the community's economy with experience and creativity and develop jobs. This study uses a qualitative case study type and uses research techniques, namely, observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. This study indicates that the strategy used by the Tempe business in business development must rely on product development strategies for creative ideas. This idea can increase the income of owners and traders where the previous trader's income was Rp. 400,000 to Rp. 600,000-Rp. 700,000 per month. Meanwhile, the inhibiting factors in the development of the MSME community and community income, especially for owners and traders, are terms of marketing, exploitation, financing, available creativity experience, work skills, years of service, and capital. But this obstacle can avoid with a reasonable and appropriate strategy